Toward Peace with Honor (1968)
This document presents the Minority Position on the Vietnam platform debate at the 1968 Democratic National Convention, advocating a shift toward "peace with honor" rather than continuation of existing policies. It argues that the minority plank represents a moderate compromise supported by respected military leaders and prominent Democrats, and calls for an unconditional halt to the bombing of North Vietnam as a necessary step toward negotiations. The proposal also supports mutual withdrawal of U.S. and North Vietnamese forces, political reconciliation within South Vietnam, and de-escalation of offensive operations to reduce casualties. In contrast, the document criticizes the majority plank as merely restating current policy, conditioning a bombing halt on reciprocal action by Hanoi, and failing to commit to de-escalation or troop reductions. It concludes that adopting the minority position would better reflect the Democratic Party's tradition of change and progress and strengthen its prospects in the general election.